A recovery mechanism based on a rewriting process for web service compositions - Toledo, Rafael Ferreira (2018)
This dissertation presents an approach to improve the robustness of Web service compositions by recovering from failures occurred at di erent moments of their execution. We rst present a taxonomy of failures as an overview of previous research works on the topic of fault recovery of service compositions. The resulting classi cation is used to propose our self-healing method for Web service orchestrations. The proposed method, based on the re nement process of compositions, takes user preferences into account to generate the best possible recovering compositions. To validate our approach, we produced a prototype implementation capable of simulating and analyzing di erent scenarios of faults. For that matter, our work uses algorithms for generating synthetic compositions and Web services. In this setting, both the recovery time and the user preference degradation are investigated under di erent strategies, namely local, partial or total recovery. These strategies represent di erent levels of intervention on the composition.